Atypical Presentation of Antiphospholipid Syndrome: A Case Report - Mariotti, Cesare; Giovannini, Alfonso; Reibaldi, Michele; Saitta, Andrea; Viti, Francesca; Nicolai, Michele (Case reports in ophthalmology, 2014)
We report an atypical presentation of Antiphospholipid syndrome (APS) with concomitant subhyaloid hemorrhage, engorged and tortuous retinal veins, intraretinal hemorrhages, and cotton wool spots in a 38-year-old female. Medical treatment was preferred to any invasive treatment. The subhyaloid hemorrhage resolved spontaneously and the patient recovered a visual acuity of 20/20 in her right eye 3 months after the initial episode. A prompt diagnosis of this condition is fundamental to consider a systemic treatment to avoid any further thrombosis.